2016
DOI: 10.1111/nep.12720
|View full text |Cite
|
Sign up to set email alerts
|

Nephrology training in Australia and New Zealand: A survey of outcomes and adequacy

Abstract: Nephrology training in ANZ generally meets clinical needs and most secure their desired employment. Training in management and research are areas for improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 19 publications
1
32
0
Order By: Relevance
“…This might also suggest that prognosis is communicated to patients infrequently. A recent survey found that 97% of Australian and New Zealand nephrology fellows over the last 10 years reported conservative care being a very important skill, but only 43% reported being well trained in it (27). This represents an area for clinical improvement, and education programs for nephrology trainees have begun to address this need.…”
Section: Discussionmentioning
confidence: 99%
“…This might also suggest that prognosis is communicated to patients infrequently. A recent survey found that 97% of Australian and New Zealand nephrology fellows over the last 10 years reported conservative care being a very important skill, but only 43% reported being well trained in it (27). This represents an area for clinical improvement, and education programs for nephrology trainees have begun to address this need.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent survey of Australian and New Zealand nephrologists within 10 years of completing fellowship echoed these findings, noting persistent concerns regarding a lack of preparedness in PD, HHD, and conservative care. 7 Notably, this survey showed no improvement in training between cohorts from 2003 to 2009 and 2010 to 2014. Both studies identified practice management and research training as additional areas for improvement.…”
mentioning
confidence: 75%
“…Few educational needs assessments of nephrology fellowships have been conducted, but the limited literature points to several areas in need of improvement. [5][6][7][8] The most recent assessment, a survey of nephrologists generally in practice for ,5 years, identified several areas in which participants felt less than well prepared, including peritoneal dialysis (PD) and home hemodialysis (HHD) modalities; performing and interpreting renal ultrasounds; end of life care; and the care of patients with pediatric kidney diseases. 6 Nephrologists felt well trained in other core areas, including in-center hemodialysis, glomerular disease, hypertension, and general CKD management.…”
mentioning
confidence: 99%
“…In a similar survey of Australian nephrologists, fewer than half of the respondents felt comfortable with automated PD (38.8%) and HHD (41.8%). 21 Rope and colleagues performed an educational needs assessment in 2017 19 to identify gaps in training for current nephrology fellows in the United States. Of the top five subjects identified (HHD, PD, kidney ultrasound, acute glomerulonephritis and obstetric nephrology), HHD (51%) and PD (45%) were identified as the areas most lacking from their training.…”
Section: Nephrology Training and Preparedness For Prescribing Home Dialysismentioning
confidence: 99%